Positioning optimization method based on indoor map deduction and signal through-wall correction - Dayang SUN; Wenxiao SHI; Dingguo ZHANG (Tongxin xuebao)
An optimization method of through-wall corrected positioning based on mixed measurements of through-wall ranging and LoS ranging was proposed to solve the problem caused by NLoS measurement error.An approximate model of through-wall measurements was first proposed aiming at the typical through-wall NLoS scenario, which made indoor positioning method independent to the factors of the signal incident angle, the structure, the dielectric constant and the thickness of the wall.Then with the help of map deduction, whether there was a wall between the to-be-located node and the anchor node could be judged, and the positioning optimization method was proposed so that localization can be solved with only the redundant measurements.Simulations and UWB experiments show that in a variable map scenario considering through-wall propagation the proposed method outperforms SR-WLS (squared-range and weighted least square) in the aspect of average accuracy of indoor positioning.